Struktur Naratif Geguritan Batur Taskara dan Potensinya Sebagai Penguatan Kurikulum Muatan - I Kadek Agus Arta Winangun (Lembaga Pengembangan Kinerja Dosen, 2024)
Geguritan is a traditional Balinese literary work in the form of a story adaptation, in the form of a pupuh song. of the many geguritan in Bali, this is the geguritan with the title Batur Taskar. The author found Geguritan Batur Taskara in the form of a book by I Made Jimbar. Geguritan Batur Taskara is sung with various songs or pupuh consisting of eight pupuh namely, pupuh sinom, pupuh ginada, pupuh pangkur, pupuh kumambang, pupuh durma, pupuh ginanti, pupuh semarandana, pupuh pangkur which are popular among the wider community, both adults and teenagers. .Based on the background above, the problems discussed in this research are 1). What is the narrative structure of Geguritan Batur Taskara 2). What is its potential to strengthen local content curriculum? The aim of this research is to describe the narrative structure and its potential to strengthen local content curriculum contained in Geguritan Batur Taskara. The theories used in this research are narrative structure theory and semiotic theory. This type of research is qualitative research, using library study methods and interview methods, supported by interview methods, reading, note-taking and triangulation techniques. Meanwhile, the method used to analyze the data is the content analysis method. In Geguritan Batur Taskara the narrative structure contained is a five-stage plot scheme in the form of introducing the story situation, revealing events, peak of tension, resolution. Batur Taskara has religious philosophical, didactic, sociological and aesthetic meaning. Therefore, what can be understood is the content of Geguritan Batur Taskara. Once understood, these values can be applied in everyday life. Geguritan Batur Taskara as a guide in living life, can also be developed, and can preserve cultural heritage as local wisdom of the Balinese people.